1975
DOI: 10.1210/endo-97-2-475
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Steroid Structure to Induction of Chymotrypsinogen in Embryonic Chick Pancreas in Vitro

Abstract: The effect of steroid structure on induction of chymotrypsinogen in embryonic chick pancreas was examined in vitro. In order of decreasing potency cortisol, corticosterone, and 21-deoxycortisol are classified as optimal inducers, whereas 11beta-hydroxyprogesterone, 11-deoxycortisol, cortisone, 11-deoxycorticosterone and 17-alpha-hydroxyprogesterone are classified as suboptimal inducers. Progesterone was inactive. It is concluded that the relative importance of the steroid hydroxyl groups for activity is 11beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
1

Year Published

1977
1977
1998
1998

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…At present the curative action of trypsin inhibitors-for example, Trasylol, Antilysin-is well established (Beck et al, 1965;Nugent and Atendido, 1965;Baden et al, 1969;Malis et al, 1972). Pancreatic tissue is characterised by a high rate of synthesis of proteins and nucleic acids (Walther et al, 1974;Cohen and Kulka, 1974). It is suggested that drugs interfering with the synthesis of these macromolecules affect the formation of pancreatic enzymes.…”
mentioning
confidence: 99%
“…At present the curative action of trypsin inhibitors-for example, Trasylol, Antilysin-is well established (Beck et al, 1965;Nugent and Atendido, 1965;Baden et al, 1969;Malis et al, 1972). Pancreatic tissue is characterised by a high rate of synthesis of proteins and nucleic acids (Walther et al, 1974;Cohen and Kulka, 1974). It is suggested that drugs interfering with the synthesis of these macromolecules affect the formation of pancreatic enzymes.…”
mentioning
confidence: 99%
“…Considerable attention has been directed towards the study of factors involved in this maturation of the pancreas. Maturation in chicks (Cohen, Heller & Kulka, 1972;Yalovsky, Heller & Kulka, 1973;Cohen & Kulka, 1974;McEvoy, Hegre & Lazarow, 1975;Kumegawa, Takuma, Ikeda, Nakanishi & Hosoda, 1979), rats (Sasaki, Mura, Takeuchi, Furihata, Matsushima & Sugimura, 1976;Takeuchi, Ogawa & Sugimura, 1977) and mice (Takuma, Nakanishi, Takagj, Tanemura & Kumegawa, 1978) has been shown to be controlled by glucocorticoid hormones. However, since the levels of these hormones in the circulation do not change apppreciably between weeks 1 and 3 after birth (Daniels, Hardy & Malinowska, 1973;Diez, Sze & Ginsburg, 1976), it would appear that some hormones other than glucocorticoids may be involved in the maturation process.…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that the administration of 0.25pmoVegg of cortisone or cortexolone had no effect on aniline hydroxylation and the elevation of TBARS levels in the liver and cataract formation. It is known that the C-1 1 positions of cortisone and cortexolone are hardly hydroxylated in chick liver (Moscona & Piddington 1967;Cohen & Kulka 1975), presumably because of lacking, or quite low activy of, 1 lp-hydroxysteroid dehydrogenase (type 1). Therefore, the phenomena described above could be caused by the biological actions of glucocorticoid since the C-11 p-hydroxyl group of the structure is known to be essential for the biological activities (Moscona & Piddington 1967;Cohen & Kulka 1975).…”
mentioning
confidence: 99%
“…It is known that the C-1 1 positions of cortisone and cortexolone are hardly hydroxylated in chick liver (Moscona & Piddington 1967;Cohen & Kulka 1975), presumably because of lacking, or quite low activy of, 1 lp-hydroxysteroid dehydrogenase (type 1). Therefore, the phenomena described above could be caused by the biological actions of glucocorticoid since the C-11 p-hydroxyl group of the structure is known to be essential for the biological activities (Moscona & Piddington 1967;Cohen & Kulka 1975). In addition, phenobarbital treatment, which stimulated hepatic hydroxylation activity of aniline in developing chick embryos at a similar rate to hydrocortisone treatment (Nishigori & Iwatsuru 1982), did not elevate TBARS in the liver and produce cataract (unpublished data).…”
mentioning
confidence: 99%